Digital Media as a New Means of Mediation (Part Two) - Rubtsova O.V., (Культурно-историческая психология, 2020)
The article continues the cycle “Digital media as a new means of mediation”. The first article of the cycle is devoted to discussing theoretical and methodological perspectives of perceiving digital media as a specific means of mediation, combining components both of a sign and of a tool. The second article highlights how some traditional types of activity are transformed in digital contexts. Particularly, peculiarities of reading hypertexts (hypermedia structures) are discussed in comparison with printed texts. A brief analysis of play activity, mediated by digital media, is presented. Characteristic traits of cyber-communication are discussed. It is argued that transformation of the existing social practices influences the social situation of development at different stages of human development and determines the contemporary socio-cultural background of the development of higher mental functions and processes. The article indicates opportunities for further research on the impact that digital media have on the development of thinking, attention and memory in users of different age groups.